ANALISIS KADAR PROTEIN, SERAT, DAN DAYA TERIMA ES KRIM DENGAN PENAMBAHAN TEPUNG SORGUM - Ristia Hanifah; Angga Hardiansyah; Dina Sugiyanti (Jurnal Ilmu Gizi Indonesia (JIGZI), 2022)
Ice cream is one of the most popular foods in the community with a fairly complete nutritional content but does not contain fiber. One alternative to increase the fiber content is to add sorghum flour which has high fiber and protein conten .This research is an experimental study with a completely randomized design (CRD), 4 treatments and 2 repetitions, formulations is F0 (0 grams), F1 (15 grams), F2 (20 grams), and F3 (25 grams).The organoleptic test was conducted by untrained panelists with a total of 30 people.Organoleptic data was collected using research questionnaires, then analyzed with the Kruskal Wallis test of the Statistics Package for the Social Science (SPSS 25). Furthermore, analysis of protein content and fiber content was carried out to then be compared with SNI.The results of the organoleptic tests on color, taste, and preference showed a significant difference (p0.05) while the aroma and texture did not show a significant difference (p0.05). Tests F0, F1, F2, and F3 protein content have results of 2.30%; 2.49%; 2.68%; 3.89%, 8.95% and fiber content; 0.04%; 0.08%; 0.04%. The protein content increased with the addition of sorghum flour, but the fiber content tended to remain unchanged. Es krim merupakan salah satu makanan yang digemari masyarakat dengan kandungan gizi yang cukup lengkap namun tidak mengandung serat. Salah satu alternatif untuk meningkatkan kadar serat adalah dengan menambahkan tepung sorgum yang memiliki kandungan serat dan protein yang tinggi. Penelitian ini merupakan penelitian eksperimental dengan Rancangan Acak Lengkap (RAL), 4 perlakuan dan 2 ulangan, formulasi F0 (0 gram), F1 (15 gram), F2 (20 gram), dan F3 (25 gram).Uji organoleptik dilakukan oleh panelis tidak terlatih dengan jumlah 30 orang.Data organoleptik dikumpulkan dengan menggunakan kuesioner penelitian, kemudian dianalisis dengan uji Kruskal Wallis Paket Statistik Ilmu Sosial (SPSS 25). Selanjutnya dilakukan analisis kadar protein dan kadar serat untuk kemudian dibandingkan dengan SNI. Hasil uji organoleptik terhadap warna, rasa, dan kesukaan menunjukkan perbedaan yang nyata (p0,05) sedangkan aroma dan tekstur tidak menunjukkan perbedaan yang nyata (p0,05). Pengujian kadar protein F0, F1, F2, dan F3 diperoleh hasil sebesar 2,30%; 2,49%; 2,68%; 3,89%, 8,95% dan kandungan serat; 0,04%; 0,08%; 0,04%. Kandungan protein meningkat dengan penambahan tepung sorgum, namun kandungan seratnya cenderung tidak berubah.